PENDIDIKAN KEMANDIRIAN DAN PERSONAL HYGIENE SANTRI PONDOK PESANTREN SHOFA MARWA - Wima Anggitasari (Jurnal SADEWA, 2025)
Pesantren is the oldest Islamic educational institution in Indonesia. Santri will learn to live independently by balancing spiritual, intellectual, moral, and skills. Santri are expected to have strong character and be able to live independently. This community service activity aims to increase knowledge about independence and personal hygiene among santri''s at the Shofa Marwa Islamic Boarding School. The method used in this activity consists of delivering material, discussion (question and answer) between participants and presenters, as well as activity evaluation consisting of pretest and posttest. This activity was attended by 30 santri''s of the Shofa Marwa Islamic Boarding School. The activity begins with a pretest which is followed by presentation of material related to independence and personal hygiene. The next stage is a posttest to evaluate the participant's level of knowledge. There is an increase in the average post test score when compared with the pre test score. The conclusion of this activity is that educational activities on independence and personal hygiene at the Shofa Marwa Islamic Boarding School are able to increase the knowledge of Shofa Marwa students regarding independence and personal hygiene.